THE IMPLEMENTATION OF LOGIC FUZZY MAMDANI METHOD AS THE DECISION SUPPORT ON THE GRADUAL SELECTION OF NEW STUDENTS - Dedy Mulyadi (The Management Journal of Binaniaga, 2018)
Gradual selection of new students at the program of Accountancy Diplome III STIE Binaniaga Bogor thru scholarship procedure using the average method. Minimum expectation of STIE Binaniaga is that the higher the gradual selection result, the better academic performance of the students will be. Applying the average method has not indicated yet the minimum expectation required since there is still the fluctuative academic achievement of the students happened. The research aims to implement the method of logic fuzzy Mamdani accordingly in order to deterimine whether this method can be applied for each gradual selection of new students. Analytical tools have used the comparison one based on the correlation between the academic achievement and the implemention of logic fuzzy Mamdani method at the end of each selection, The correlation between the cumulative achievement index and the final result of the implemention of average method is 0.559. Correlation between the cumulative achievement index and the final result of the implementation of logic fuzzy Mamdani Method is 0.487 which is still less than 0.559. Nevertheless, the conclusion of this result is that the implementation of logic fuzzy Mamdani Method has not yet been able to replace the existing average method. Keywords: gradual selection, comparison, linear correlation, logic fuzzy Mamdani.